Transgenics in crop improvement research at IITA - Tripathi, L. (2012)
Biotechnology has opened unprecedented avenues for exploring biological systems. Transgenics is one of the key techniques particularly useful for the genetic improvement of crops that are not amenable to conventional breeding, such as those that are vegetatively propagated. In IITA, transgenic technologies are being used for improving banana/plantain (Musa sp.), cassava (Manihot esculenta), and yam (Dioscorea sp.).